Heterosis and combining ability of elite maize inbred lines under northern corn leaf blight disease prone environments of the mid-altitude tropics - Abera, W.; Hussein, S.; Derera, J.; Worku, M.; Laing, M. (Springer, 2016)
Yields of maize (Zea mays L.) are remarkably low in sub-Saharan Africa and yet farmers have limited access to improved varieties. The objective of this study was to determine combining ability and heterosis of 18 elite maize inbred lines in environments prone to northern corn leaf blight (NCLB) disease in the mid-altitude tropics. Nine elite inbred lines were crossed as females with nine male lines using the North Carolina Design II mating scheme and 81 hybrids were generated. The hybrids, parents and three standard check varieties were evaluated using an alpha lattice design with two replications across seven environments in the mid-altitude sub-humid agro-ecologies in Ethiopia. The new top ranking hybrids displayed up to 250 % high-parent heterosis and mid-parent heterosis for grain yield and up to −25 % high-parent mid-parent heterosis for NCLB reaction. The specific combining ability (SCA) by site interaction was not significant, suggesting that the top yielding hybrids were relatively stable across environments. Inbred lines such as CML 395, 30H83-7-1, ILO’OE-1-9, 124-b (113), CML202, CML312, and Gibe-1-91 resulted in significant SCA effects for grain yield were selected as promising parents. Lines CML395 and ILO’OE-1-9 had negative and significant general combining ability (GCA) effects for NCLB reaction, implying the resistance of the inbred lines for NCLB. The most performing experimental hybrids such as CML-312 × CML395, CML197 × CML395, CML443 × DE-78-Z-126-3 had high SCA effects and produced mean grain yields of >8 t ha−1. The new hybrids may be used directly for production or as testers in hybrid development with resistance to NCLB.